Application of winning mentality in the ideological and political education of college physical education students - Junjie Li; Xiurong Zhang , (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Chinese physical education aims to improve students' physiques gradually, enable them to grasp specific fitness knowledge and skills, and encourage their physical and mental health growth. A questionnaire study of 470 college students in physical education is administered to determine the application of winning psychology in college physical education students' ideological and political education (PE). In addition, SPSS 17.0 was employed for the statistical analysis. According to the results, male and female college students exhibited dramatically different opinions toward doping. Males were likelier to dope than girls (p<0.05) and were more susceptible to coach, teammate, and environmental pressure. Moreover, it is stated that teachers should not only convey their knowledge and skills but also teach students by words and acts during the teaching process, infect students with their charismatic personalities, and teach students how to behave. In conclusion, it is emphasized that the most significant difference between physical education instruction and traditional ways of teaching other courses is that there is almost no distance between professors and students, and students will even compete with their teachers in sports.